Preparation of conductive polymer composites for micro fuel cells (II) - Thwe, Myo Myo. (2011)
This project is aimed on the preparation of the binary and ternary composites of polyamide 66 (PA66), conductive carbon black (CCB) and multi-walled carbon nanotubes (MWCNTs) fabricated by a melt-mixing technique for micro fuel-cell application.